Past distribution (21,000 yrs) of the ground beetle Pelmatellus columbianus in Ecuador - Sofia Isabel Munoz-Tobar (PANGAEA, 2018)
This dataset contains raster grids in TIFF format describing the past distribution (21000 yrs) of Pelmatellus columbianus in continental Ecuador. The spatial resolution is 2.5 m x 2.5 m.